LRH1 Promotes Tumor Cell Proliferation and Migration and Is Correlated With Poor Prognosis in Ovarian Cancer - Sun, Wenzhou; Shi, Qingtao; Li, Jiaxin; Li, Jinmeng; Yu, Libo (Frontiers in Oncology, 2020)
Background Liver receptor homolog 1 (LRH1) plays a vital role in several human cancers, but its role in ovarian cancer (OC) remains unclear. We aimed to explore the functions of LRH1 and its clinical relevance. Methods LRH1 expression was evaluated by immunohistochemistry and reverse transcription quantitative polymerase chain reaction (RT-qPCR). The effects of LRH1 on tumor cell proliferation, migration and epithelial-mesenchymal transition (EMT) were evaluated in vitro. Furthermore, bioinformatics analysis was applied to predict the functions of LRH1. Results RT-qPCR showed that LRH1 mRNA expression was more higher in the invasive lesions (P < 0.05). LRH1 overexpression was extremely related with elevated International Federation of Gynecology and Obstetrics (FIGO) stage (P = 0.001), lymph node metastasis (P = 0.011), peritoneal metastasis (P = 0.001), and platinum resistance (P = 0.037). Furthermore, LRH1 expression was an independent prognostic index for disease-free survival in patients with OC (P = 0.041). LRH1 overexpression (P=0.011), FIGO stage (P<0.001), and ascites (P=0.015) independently affected peritoneal metastasis in patients with OC. LRH1 knockdown significantly inhibited the proliferation, migration, and EMT of human OC cells (P < 0.05), however, reversed the cisplatin resistance. Bioinformatics analysis indicated that the functions of LRH1 were associated with the PRC1 complex, nuclear ubiquitin ligase complex, and Polycomb-group (PcG) proteins. Conclusions This study provides evidence of the predictive value of LRH1 on peritoneal metastasis and poor outcome and highlights the potential role of LRH1 as a biomarker for the targeted therapy of OC. Furthermore, LRH1 promotes OC cell proliferation, migration, and EMT in vitro, and its functions may be associated with PRC1 complex, nuclear ubiquitin ligase complex, and PcG proteins.